2018
DOI: 10.1186/s13638-018-1050-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of energy-harvesting-aware multi-relay networks in Nakagami-m fading

Abstract: This paper investigates the outage performance of an energy-harvesting(EH) relay-aided cooperative network, where the source node transmits information to its destination node with the help of multiple energy-harvesting cooperative nodes. For such a system, we derive an explicit closed-form expression of outage probability over Nakagami-m fading channels, where the on-off EH model is considered. We simulate the explicit closed-form expression of outage probability with different parameters compared with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…N) is independent identically distributed (i.i.d.). Meanwhile, by using (5) and 7, the PDF of γ s,i can be written as…”
Section: Os/sc Schemementioning
confidence: 99%
See 2 more Smart Citations
“…N) is independent identically distributed (i.i.d.). Meanwhile, by using (5) and 7, the PDF of γ s,i can be written as…”
Section: Os/sc Schemementioning
confidence: 99%
“…Satellite communication (SatCom) has the potential of providing connectivity for fixed and mobile users especially in the areas where the terrestrial networks are challenging or infeasible to be deployed [1][2][3][4]. Meanwhile, it has been shown that relay technology is able to offer significant performance benefits, such as improving the system throughput via spatial diversity, extending signal coverage without consuming large transmitter power [5]. Therefore, the application of relay transmission in SatCom has been an active research topic both in academia and industry recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Zhong et al investigated the outage performance of an EH relay network in which the BS transmits information to the SNs with the help of multiple ERs by using the AF technique. These authors concluded that the outage performance of the system can be improved by employing EH ERs [25].…”
Section: Introductionmentioning
confidence: 99%
“…An SN can collect energy from ambient RF signals to power its operations. RF EH is especially attractive for relay WSNs that rely on ERs to extend their coverage areas and improve their system performance [23]- [25]. For instance, A. Nasir et al considered the application of RF EH in relay WSNs based on two practical receiver architectures for EH, namely, time-switching-based relaying (TSR) and power-splitting-based relaying (PSR) [23].…”
Section: Introductionmentioning
confidence: 99%